Integrated impacts of tree planting and street aspect ratios on CO dispersion and personal exposure in full-scale street canyons. (February 2020) - Yang, Hongyu; Chen, Taihan; Lin, Yuanyuan; Buccolieri, Riccardo; Mattsson, Magnus; Zhang, Ming; Hang, Jian; Wang, Qun
Abstract: Validated by experimental data, this paper performs computational fluid dynamics (CFD) simulations to investigate the influence of tree plantings on urban airflow and vehicular CO exposure in two-dimensional (2D) street canyons with various aspect ratios (building height/street width, AR = H/W = 0.5, 1, 3, 5) and ground-level source. The impacts of tree canopy bottom height ( Htb = 2 m, 6 m), tree stand density ( y-density = 0.33, 0.67, 1) and leaf area density ( LAD = 0.5, 1, 2 m 2 /m 3 ) are considered. Personal intake fraction ( P_IF ) and its spatial mean value in leeward and windward sides (< P_IF> lee, < P_IF> wind ) and for entire streets (street intake fraction, < P_IF> ) are adopted to assess overall pollutant exposure. For cases without trees, only one main vortex exists in shallow streets with AR = 0.5-3 and < P_IF> as AR = 3 (5.80 ppm) slightly exceeds AR = 0.5-1 (3.98-3.84 ppm). However, two counter-rotating vortexes appear in deep streets ( AR = 5), inducing 1-2 orders smaller pedestrian-level velocity ( U /U ref 10 −4 -10 −3 ) and one-order greater < P_IF> (46.80 ppm) than shallow streets. Trees always weaken wind in streets and raise more in shallower streets by 46.0% as AR = 0.5 (3.98 ppm-5.81 ppm), 26.0-45.9% as AR = 1 (3.84 ppm to 4.84-5.60 ppm), 16.2-50.3% as AR = 3 (5.80 ppm to 6.74-8.72 ppm), but only 8.5-23.4% as AR = 5 (46.80 ppm to 50.78-57.73 ppm). Particularly, as AR = 1, trees raise < P_IF >lee (5.87 ppm) by 27.1-57.2%, while < P_IF >wind (1.80 ppm) only by 0%-23.3%. Higher Htb, smaller y-density or LAD produce less increase of . As AR = 3, vegetation increases lee (8.84 ppm) by 21.2%-66.4% but little affects wind (2.76 ppm). Lower Htb produces smaller < P_IF> differing from AR = 1. As AR = 5, vegetation increases wind (63.97 ppm) by 15.1-36.6% but reduces lee (29.63 ppm) by 5.2-8.5%. Although further investigations are still required for design purpose, this paper provides effective methodologies to quantify how vegetation influences street-scale pollutant exposure. Graphical abstract: Image 1 Highlights: Personal intake fraction ( P_IF ) quantifies pollutant exposure with various H/W s. As H/W = 5, < P_IF> ( 50 ppm) is 1-order larger than H/W = 0.5, 1, 3 ( 4–6 ppm). Trees weaken ventilation and raise < P_IF> by 16–50% as H/W = 0.5–3, 9–23% as H/W = 5. Trees raise leeward-side C more than windward as H/W = 0.5–3 but opposite as H/W = 5. Trees affect the whole canyon as H/W = 1 but area below 16th, 7th floor as H/W = 3, 5.